2003
DOI: 10.1046/j.1532-5415.2003.51461.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Evercare on Hospital Use

Abstract: The use of active primary care provided by NPs may have prevented the occurrence of some hospitalizable events, but its major effect was allowing cases to be managed more cost-effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
242
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(252 citation statements)
references
References 14 publications
5
242
0
3
Order By: Relevance
“…11 A corroborative inquiry found that subsequent hospitalization rates were cut almost in half when nurse practitioners directly managed the primary care of nursing home residents. 12 A recent 3-year study of worksite health clinics suggested that every dollar spent on nurse practitioners saved several dollars that otherwise would have been spent for physician treatment of major diagnostic conditions. 13 A study in Tennessee found that costs at nurse practitioner-managed practices were 23% below the costs of care delivered by other primary care providers; inpatient hospitalization rates were 21% lower.…”
Section: The Cost Side Of the Equation: Advantage Of Nurse Practitionersmentioning
confidence: 99%
“…11 A corroborative inquiry found that subsequent hospitalization rates were cut almost in half when nurse practitioners directly managed the primary care of nursing home residents. 12 A recent 3-year study of worksite health clinics suggested that every dollar spent on nurse practitioners saved several dollars that otherwise would have been spent for physician treatment of major diagnostic conditions. 13 A study in Tennessee found that costs at nurse practitioner-managed practices were 23% below the costs of care delivered by other primary care providers; inpatient hospitalization rates were 21% lower.…”
Section: The Cost Side Of the Equation: Advantage Of Nurse Practitionersmentioning
confidence: 99%
“…Involvement of NPs and PAs in collaboration with primary care physicians has repeatedly been shown to be associated with less hospitalization of NH residents. [12][13][14][23][24][25] Involving these health professionals in care transition interventions in which acute hospitals collaborate with NHs and home health agencies would build upon evolving models, 26,27 but the number of healthcare professionals with special training and interest in geriatrics and long-term care medicine is not increasing rapidly enough to meet this need. 28 Financial incentives to obtain certification in geriatrics or work in NHs, such as loan repayment programs, and the development of a specialty in NH medicine 29 may help in this regard.…”
mentioning
confidence: 99%
“…The unreimbursed costs, as well as the potential regulatory and legal liabilities of caring for sicker residents, are potent disincentives to managing residents with acute changes in status in the NH. [19][20][21][22] Managed care programs such as Evercare and others mitigate these financial incentives and have been shown to reduce hospitalization of NH residents when teams of physicians and NPs or PAs provide more care in the NH, 14,23,24 but the number of NH residents in these programs remains small.…”
mentioning
confidence: 99%
“…One potential explanation for this is that in addition to the staff investment, the reduction in potentially avoidable hospitalization may need nursing homes to invest in the clinical resources (e.g. diagnostic services, nurse practitioners/physician assistants, intravenous therapy) so as to manage the residents' acute care needs on-site [29, [183][184][185][186], or make specific changes in practice such as improvement in preventive services, chronic disease management, to prevent the need for hospitalization. Furthermore, nursing homes have no clear incentives to reduce the likelihood of hospitalization as hospital services are paid by Medicare.…”
Section: Changes In Quality Of Nursing Home Carementioning
confidence: 99%